2022
DOI: 10.1002/jsfa.12329
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine‐based liposome to improve oral absorption and nephroprotective effects of astaxanthin

Abstract: BACKGROUND The present study was aimed to develop astaxanthin (AX)‐loaded liposomes by the utilization of soybean phosphatidylcholine (PC) and lysophosphatidylcholine (LPC) to improve the nutraceutical properties of AX. AX‐loaded liposomes consisting of PC (PC/AX) and LPC (LPC/AX) were evaluated in terms of particle size distribution, morphology, release characteristics, pharmacokinetic behavior, and nephroprotective effects in a rat model of acute kidney injury. RESULTS PC/AX and LPC/AX had uniform size distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This negative charge could be attributed to free fatty acids on the surface of emulsions derived from MCT, which may prevent particle aggregations due to the electric repulsion between particles 42 . As per a prior study, colloidal dispersions exhibit favorable stability when their zeta potential is high and negative, exceeding −20 mV 43 . This is because of the electric repulsion between the particles.…”
Section: Physicochemical Characterizations Of Smedds-glesupporting
confidence: 63%
See 1 more Smart Citation
“…This negative charge could be attributed to free fatty acids on the surface of emulsions derived from MCT, which may prevent particle aggregations due to the electric repulsion between particles 42 . As per a prior study, colloidal dispersions exhibit favorable stability when their zeta potential is high and negative, exceeding −20 mV 43 . This is because of the electric repulsion between the particles.…”
Section: Physicochemical Characterizations Of Smedds-glesupporting
confidence: 63%
“…Cisplatin can penetrate renal epithelial cells via organic cation transporter 2 (OCT2) and copper transporter 1 (Ctr1), leading to mitochondrial DNA damage and elevated levels of reactive oxygen species (ROS). This ultimately leads to tubular apoptosis and necrosis 43,52 . The kidney tissues were examined under a light microscope after 72 h of cisplatin exposure.…”
Section: Nephroprotective Function Of Gle Samplesmentioning
confidence: 99%
“…It was found that in the presence of LPC, the SUVs were smaller, and the LMVs had less leakage, but LPC did not exert any significant effect ( p > 0.05) on the transfer of carboxyfluorescein to the lymphocytes. A recent investigation [ 109 ] used LPC and phosphatidylcholine (PC) for the manufacture of liposomes in order to improve nephroprotective effects and the oral absorption of astaxanthin. The authors reported that at a pH close to neutral (pH 6.8), such liposomes exhibited an improved dissolution behaviour of astaxanthin when compared to the behaviour of untreated/crystalline astaxanthin.…”
Section: Lpc For the Delivery Of Other Bioactive Ingredientsmentioning
confidence: 99%
“…Particularly, the release of astaxanthin from the liposome-containing LPC was seven-fold higher than that of those manufactured using PC, besides a significant increase ( p < 0.05) in systemic exposure to astaxanthin (a 15-fold higher after 24 h after oral administration), when compared to liposomes made of PC. Based on the results obtained from histological analysis and plasma biomarkers in the rat model of kidney injury, the researchers concluded that the LPC-based liposomes exhibited the improved nephroprotective effects of astaxanthin [ 109 ]. Therefore, these findings suggest that an LPC-based liposomal approach might provide a sustainable option for improving the bio-efficacy of astaxanthin, which may be applicable to other lipophilic bioactive ingredients as well.…”
Section: Lpc For the Delivery Of Other Bioactive Ingredientsmentioning
confidence: 99%